The Local Community's Perspective: Development of Tengkudak Village as A Tourist Village - Oka, I Made Darma; Suparta, I Ketut; Budiasa, I Made; Suarja, I Ketut; Darmayanti, Putu Widya (Journal of Hospitality Accommodation Management (JHAM), 2025)
This research aims to explore the potential for developing Tengkudak village as a tourist village from the perspective of the local community. Data collection through observation, interviews, and literature study using quantitative descriptive analysis. The sample was determined as 100 people through proportional random sampling. Informants were selected from the community who understood the existence of the village through proportional random sampling. The research results show that the local community basically strongly agrees with developing this village as a tourist village, with a score of 4.11 (agreeing to develop it into a tourist village). To be able to maximize the development of the tourist village, it is necessary to involve pentahelic actors (government, academics, tourism actors, the media, and local communities) in the development of the tourist village. The government is only limited to facilitating, and local communities are the main actors in developing tourist villages, so they can better understand natural and cultural phenomena, as a determinant of the quality of tourism products owned by the village. This can certainly foster a common perception of all Pentahelix actors and provide the widest possible space for local communities as the main actors in developing tourist villages.